Successful repeat ECMO in a patient with AIDS and ARDS - Horikita, Sho (BMJ Case Rep, 2017)
Veno-venous extracorporeal membrane oxygenation (ECMO) is being more commonly used in patients with acute respiratory distress syndrome (ARDS) due to potentially reversible illnesses. Survival from ARDS using ECMO has been reported even in patients with AIDS. However, the indications for ECMO for ARDS due to immune reconstitution inflammatory syndrome (IRIS) in patients with AIDS are unknown. A 23-year-old man with AIDS and Pneumocystis jirovecii pneumonia was admitted to the intensive care unit with severe ARDS refractory to mechanical ventilator support requiring ECMO. Although ECMO was discontinued, a second treatment with ECMO was necessary due to IRIS-associated ARDS, resulting in an excellent patient outcome. This patient’s clinical course suggests two important messages. First, ECMO is a reasonable option for the treatment of patients with ARDS even in a patient with AIDS. Second, ECMO may be effective for the treatment of patients with IRIS.